The Climate Change Issue towards Behavioral Intentions: A Perspective of Social Marketing - Aryanto, Vincent Didiek Wiet; Wismantoro, Yohan; Paramitadevi, Yudith Vega (International Journal of Energy Economics and Policy, 2020)
This study aims at investigating the online social marketing on climate change and global warming towards behavioral intentions among youngsters in Indonesia. The model of online social marketing composed of perceived ethical capability as mediation variable, trust and commitment. The online social marketing on climate change has significant impact on behavior intentions through perceived ethical capability as mediation variable; trust and commitment have also significant impact on behavior intentions. The purposive sampling method was utilized among 239 respondents. Model of Structural Equation (SEM) version 23 was used to test the hypotheses. This study might be contributing to the body of knowledge particularly the advancement and effectiveness online social marketing on climate change and its impact on behavior intentions. Keywords: Online social marketing, climate change, perceived ethical capability, trust, commitment and behavior intentions. JEL Classifications: M31, P28 DOI: https://doi.org/10.32479/ijeep.8820